Understanding BRICS / Syazliana Kasim - Kasim, Syazliana (Universiti Teknologi MARA Cawangan Negeri Sembilan Kampus Rembau, 2024)
BRICS is an acronym for an association of five major emerging economies: Brazil, Russia, India, China, and South Africa. Initially coined as "BRIC" in 2001 by economist Jim O’Neill of Goldman Sachs, the grouping originally included only Brazil, Russia, India, and China. These countries were highlighted for their rapidly growing economies and potential to significantly influence global economic trends. In 2010, South Africa was added to the group, leading to the current BRICS configuration. This collective of nations represents a significant portion of the world’s population, landmass, and economic output, positioning it as a formidable force in global politics and economics. This article explores the historical development, economic impact, political influence, and future prospects of BRICS.